On variability of total ozone derived from TOVS data over peninsular Indian sub-continent and adjoining oceanic area - SURESH, R. (MAUSAM, 2002)
The total ozone derived from TOVS data from NOAA 12 satellite through one step physical retrieval algorithm of International TOVS Processing Package (ITPP) version 5.0 has been used to identify its diurnal, monthly, latitudinal and longitudinal variability during 1998 over the domain Equator to 26° N / 60-100° E. The linkage of maximum total ozone with warmer tropopause and lower stratosphere has been re-established. The colder upper tropospheric temperature which is normally associated with maximum ozone concentration throughout the year elsewhere in the world has also been identified in this study but the relationship gets reversed during southwest monsoon months(June-September) over the domain considered. The moisture available in abundance in the lower troposphere gets precipitated due to the convective instability prevailing in the atmosphere during monsoon season and very little moisture is only available for vertical transport into the upper troposphere atop 500 hPa. The latent heat released by the precipitation processes warms up the middle and upper atmosphere. The warm and dry upper troposphere could be the reason for less depletion of ozone in the upper troposphere during monsoonal months and this is supported by the positive correlation coefficient prevailing in monsoon season between total ozone and upper tropospheric (aloft 300 hPa) temperature. The warmness in middle and upper troposphere which is associated with less depletion and/or production of more ozone in the upper troposphere may perhaps contribute for the higher total ozone during monsoon months than in other seasons over peninsular Indian region. The minimum concentration is observed during January (226 DU) over 6° N and the maximum (283DU) over 18° N during August. Longitudinal variability is less pronounced than the latitudinal variability.